Japanese Short Poem Senryū’s: A Perspective from the “Superiority Theory of Humor” - Dogan, Guliz (European Scientific Journal, ESJ, 2025)
Senryū is a Japanese short poem written in 5-7-5 syllables and reflects the various aspects of human life in a humorous or satirical way. Every year, numerous senryū competitions covering various topics are held in Japan. Dai-ichi Life Insurance Company’s senryū competition (サラっと一句！わたしの川柳コンクール/Saratto ikku! Watashi no Senryū Konkūru) (old name: サラリーマン川柳(Sararīman Senryū/Salaryman Senryū)) is the most popular and longest-running competition in Japan. In this competition, people express what they experience daily and the difficulties they encounter in business, etc. So, in the present study, the poems compiled from Dai-ichi Life Insurance Company’s Senryū Competition in the years 1990-2020 related to family relations will be analyzed from the perspective of the Superiority Theory of Humor. This theory can be identified as a feeling oneself superior to others’ mistakes and misfortunes. In conclusion, the Superiority Theory of Humor is seen in most of the senryū poems. The topics are behind the technology and trends, which are below the beauty standards of society, such as being ugly and fat. The reader feels superior by experiencing a sudden victory that he/she has not experienced the above-mentioned bad situations himself/herself.